Association between sociodemographic factors and noncavitated and cavitated caries lesions in 8- to 12-year-old Mexican schoolchildren - Garcia Perez, Alvaro; Cuevas-González, Juan Carlos; Gonzalez Aragon Pineda, Alvaro Edgar; Rosales Ibañez, Raul; Rodriguez Chavez, Jaqueline Adelina; Perez Perez, Nora Guillermina; Villanueva Gutierrez, Teresa (2021)
The aim of this study was to evaluate the association between sociodemographic factors and noncavitated and cavitated caries lesions in Mexican schoolchildren. This cross-sectional study was conducted in 2020 on 8-to-12-year-old schoolchildren of different socioeconomic status (SES). The caries was evaluated using ICDAS II, SES was evaluated using three categories—a high, middle, or low-income level—of the CONAPO. Multinomial logistic regression analyses were performed in order to ascertain the associations between socioeconomic factors and noncavitated and cavitated caries lesions. The prevalence of noncavitated lesions was 38.0% and cavitated lesions was 43.4% in permanent dentition. In all the samples, 50.6% of schoolchildren had poor oral hygiene. About 52.5% of the mothers and 64.7% of the fathers had less than 9 years of education. Schoolchildren with a low-income level have more cavitated lesions (ICDAS II 4–6) than schoolchildren with high-income level (56.3% vs 15.8%, P=.009). The multinomial logistic regression models showed that mother’s level of education <9 years and low-income level were significantly associated with cavitated caries lesions (ICDAS II 4–6), [odds ratio=1.79 (1.17 – 2.75); P=.007], [OR=2.21 (1.23 – 3.97); P=.008], respectively. The socioeconomic level was not associated with noncavitated caries lesions (ICDAS II 1–3).